2004
DOI: 10.1016/s0092-8674(04)00163-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA Deamination Mediates Innate Immunity to Retroviral Infection

Abstract: The May 28, 2003 immediate early online version of this article (Cell 113, 803-809, 13 June 2003) contained one sentence that did not appear in the printed version. In the results subsection entitled "CEM15/APOBEC3G Is Incorporated into MLV Virions," a bracketed sentence appeared in the following context: The CEM15/APOBEC3G-mediated suppression of HIV infection is thought to be accomplished by protein transferred as a virion component from virus producing cells into target cells (curiously, such physical trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
595
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(631 citation statements)
references
References 0 publications
30
595
1
5
Order By: Relevance
“…To detect edited elements, we assumed that a newly edited element should be almost identical to its ancestral element except for a few dense clusters of G-to-A mismatches, as such clusters are the hallmark of APOBEC3 editing [10][11][12][13] . To confirm that the mismatches are due to DNA editing, we exploited the asymmetry, or strand specificity, of editing: as opposed to random mutagenesis, APOBEC3 generates C-to-U mutations specifically on the negative strand of the element (with respect to the ORF), yielding clusters of G-to-A mutations, but not C-to-T, on the positive strand [10][11][12] .…”
Section: Identification Of Editing Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…To detect edited elements, we assumed that a newly edited element should be almost identical to its ancestral element except for a few dense clusters of G-to-A mismatches, as such clusters are the hallmark of APOBEC3 editing [10][11][12][13] . To confirm that the mismatches are due to DNA editing, we exploited the asymmetry, or strand specificity, of editing: as opposed to random mutagenesis, APOBEC3 generates C-to-U mutations specifically on the negative strand of the element (with respect to the ORF), yielding clusters of G-to-A mutations, but not C-to-T, on the positive strand [10][11][12] .…”
Section: Identification Of Editing Sitesmentioning
confidence: 99%
“…To confirm that the mismatches are due to DNA editing, we exploited the asymmetry, or strand specificity, of editing: as opposed to random mutagenesis, APOBEC3 generates C-to-U mutations specifically on the negative strand of the element (with respect to the ORF), yielding clusters of G-to-A mutations, but not C-to-T, on the positive strand [10][11][12] . We therefore aligned, pairwise, the positive strands of all retrotransposons from selected families, and scanned the alignments for windows containing a particularly large number of G-to-A mismatches but no mismatches of any other type (Fig.…”
Section: Identification Of Editing Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular nature of permissivity and the exact function of Vif in infection of nonpermissive cells was not known until recently when a series of reports showed that a host cellular protein known as APOBEC3G (apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3G) is a potent inhibitor of HIV infection in the nonpermissive cells [70,71]. APOBEC3G is a member of the cytidine deaminase family, which prevents viral cDNA synthesis via deaminating deoxycytidines (dC) in the minus-strand retroviral cDNA replication intermediate [72][73][74][75][76]. As a result, it creates stop codons or G-A transitions in the newly synthesized viral cDNA which is then subjective to elimination by host DNA repair machinery [74,76].…”
Section: Virus Infectivity Factor (Vif)mentioning
confidence: 99%
“…81,82 The human APOBEC3 members act during reverse transcription by deaminating C to U in single-stranded viral cDNA, which induces guanine to adenine mutations in the complementary cDNA strand. 83 To function, human APOBEC3G is packaged into virions in producer cells but blocks viral replication in target cells (discussed in Harris and Liddament 75 ), most likely by degrading the viral cDNA between late reverse transcription and integration. 84 In defense, the lentiviruses use their viral infectivity factor (Vif) accessory protein to prevent APOBEC3 packaging into virions in producer cells and circumvent restriction in target cells (reviewed in Anderson and Hope 30 and Harris and Liddament 75 ).…”
Section: Avoiding Host Cell Restrictionsmentioning
confidence: 99%